The Strength of Islamic Bank in Nigeria Facing the Economic Crisis - Zuri, Nkechi; Chuka, Emeka Ifeanyi (Institut Agama Islam Sunan Giri Ponorogo, 2023)
Time is ticking and times of economic crisis will continue to recur with various causes that may be different and require different solutions to problems. In Nigeria, there was an economic crisis to a food crisis, this was also triggered by the Covid-19 Pandemic, this crisis began to be felt in 2020. The research method used in this research is to use descriptive qualitative analysis. No one expects an economic crisis anywhere and anytime. Nigeria is known as a country prone to racial and religious conflicts. In 2020, the capital city of Borno state often faced conflicts between civilians. Deputy head of the UN Office for the Coordination of Humanitarian Affairs (OCHA) Nigeria, Esty Sutyoko, said Nigerians have lost their livelihoods for more than a decade. This was triggered by violence and the Covid-19 pandemic as well as food insecurity in the region. The Covid-19 pandemic began with reports of cases of pneumonia (pneumonia) with unknown causes in Wuhan, China at the end of December 2019. But on the other hand, Islamic banking has again proven that the system used is really resistant to crises, not just theory and coincidence because it has been proven three times through economic crises and the power of Islamic banking is very strong to beat conventional banking.